Cultivating Mindfulness Activities to Develop Peaceful Well-being - Jiwattanasuk, Narumon; Premsakul, Kittiched; Tanpoonkiat, Woraponte; Deegalle, Mahinda (Journal of International Buddhist Studies, 2024)
Looking for ways to cultivate greater peace and well-being in your life? Consider the ancient Buddhist practice of mindfulness. We present mindfulness as the art of cultivating “awareness of the present.” Our article offers practical tips for incorporating mindfulness into your daily routine, with an emphasis on promoting peaceful, positive states of mind. While we discuss the concept of peaceful well-being from a Buddhist perspective, we recognize that mindfulness is a practice that can benefit anyone, regardless of background or belief system. We provide a useful analysis for understanding and easy measurement of peaceful well-being. Research has demonstrated that mindfulness can enhance physical, mental, and cognitive well-being. By integrating mindfulness into activities such as walking, sitting, or eating, you can enjoy the many benefits of this transformative practice. Based on evidence-driven research projects in cultivating mindfulness practices, this paper enables practitioners to create peaceful well-being.